Linguistic Readiness of Doctoral Candidates: A Case Study of TOEFL Policy at the Faculty of Agriculture - Ruminar, Hafida; Gayatri, Putri (Universitas Dian Nuswantoro, 2024)
English language proficiency is critical for doctoral candidates, particularly in non-English-speaking countries like Indonesia, where mastery of reading and writing in English is essential for academic success. This study evaluates the effectiveness of TOEFL scores as indicators of doctoral students' abilities to comprehend and produce scientific texts in English. However, few studies have investigated how TOEFL scores represent doctoral students’ reading and writing abilities in scientific texts from the viewpoints of the individuals directly engaged. Thus, this qualitative study addresses the research gap by employing semi-structured interviews with four doctoral students from the Faculty of Agriculture at a public university in Malang, Indonesia, and the Head of the Doctoral Study Program. The data were analyzed inductively using Bloom's taxonomy to assess the depth and complexity of the participants' linguistic readiness. The results were then classified based on the Bloom Taxonomy level from the fundamental knowledge comprehension to the creation of doctoral candidates' scientific articles. The study's findings underscore the need for more comprehensive assessments of English proficiency in postgraduate admissions. While higher TOEFL scores generally indicate better comprehension and writing skills, they do not consistently reflect the specific competencies required for scientific writing. This suggests that the TOEFL score may be insufficient as a sole metric for linguistic readiness. The study contributes to policy discussions by highlighting this need, particularly in disciplines requiring specialized academic writing skills.